Significance of Plasma Dopamine β-Hydroxylase Activity as an Index of Sympathetic Neuronal Function - Reid, John L. (1974)
Plasma norepinephrine and dopamine β-hydroxylase (EC 1.14.17.1) activity were measured in rats. Adrenergic neuron blockade with bretylium for 4 hr and ganglion blockade with chlorisondamine for 72 hr lowered plasma norepinephrine. Neither treatment altered plasma dopamine β-hydroxylase activity. Phenoxybenzamine for up to 48 hr markedly raised plasma norepinephrine and transiently lowered plasma dopamine β-hydroxylase at 24 hr. Prolonged pharmacological modification of sympathetic nervous activity and plasma norepinephrine were not attended by parallel changes in circulating dopamine β-hydroxylase activity. Plasma dopamine β-hydroxylase activity does not appear to be a sensitive index of prolonged alterations in sympathetic neural activity. Norepinephrine in plasma, however, appears to reflect sensitively and accurately the rate of release of the neurotransmitter.